Managing a Challenge Case: Transesophageal Echocardiography-Guided Transcatheter Closure of a Large Secundum Atrial Septal Defect in a Pregnant Woman - Fathoni, Emil; Martini, Heny; Rahimah, Anna Fuji; Putri, Valerinna Yogibuana Swastika (Universitas Brawijaya, 2024)
Background: The management of complex cardiovascular conditions during pregnancy poses unique challenges, and in the case of a large secundum atrial septal defect (ASD), achieving successful closure through a transcatheter approach guided by transesophageal echocardiography (TEE) requires careful navigation and expertise. This study sought to present a case that exemplifies the contemporary approach of using TEE guidance for the closure of an ASD in pregnant womenCase presentation: A 31-year-old woman with multigravida, diagnosed with secundum ASD and pulmonary hypertension, underwent TEE. The TEE examination revealed a significant ASD measuring 2.8-3.1 cm with inadequate surrounding rims. Subsequently, our intention was to employ a device to address this defect. TEE was utilized to guide the placement of a 14F delivery sheath into the left upper pulmonary vein and left atrium. Using a catheter, we successfully deployed a 40 mm ASD Occluder (MemoPart), concluding the intervention without any complications. Given the concerns regarding the potential risks of radiation exposure and teratogenic effects on fetal development, particularly in young patients and during pregnancy, it is crucial to prioritize TEE-guided closure of ASD for the safety of both the mother and the fetus.Conclusion: Closure of ASD with zero fluoroscopy proved to be a safe and effective procedure, demonstrating feasibility and significant benefits for pregnant women with ASD.